Giant days. Volume fourteen - Allison, John, 1976-; Allison, John, 1976- (BOOM! Box, 2020)
"THE END IS HERE! KINDA! Return to Sheffield one last time as Daisy and Esther are about to graduate - with Susan there to cheer them on! But it's not goodbye, because one year later Daisy and Susan must join forces to save Esther from the head girls who're making her life hell! And then it really might just be goodbye..."--Provided by publisher.